COMPARATIVE STUDY BETWEEN POSTOPERATIVE ANALGESIC EFFECTS OF ADDING INTRAINCISIONAL MEPERIDINE VERSUS INTRAINCISIONAL TRAMADOL TO BUPIVACAINE IN ELECTIVE CESAREAN SECTION UNDER SPINAL ANESTHESIA - Mahmoud Ahmed Abdel Salam; Medhat Helaly Allam; Mohamed Mohamed Abo Elenin; Mohammed Al-Saeed Abdo Abu Hatab (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Background: Analgesic treatment has traditionally focused on central mechanisms associated with pain perception via the use of opioids. The aim of this work was to evaluate the postoperative analgesic effect of intra-incisional infiltration of meperidine added to bupivacaine versus tramadol added to bupivacaine in elective cesarean section (CS) under spinal anaesthesia. Methods: This randomised controlled double blinded work had been conducted on 90 healthy full-term patients aged from 20 to 35 years old, planned for elective CS under spinal anaesthesia. Patients were divided into three equal groups: Meperidine Group: obtained 50 mg meperidine with 50 mg bupivacaine, Tramadol Group: received 50 mg tramadol with 50 mg bupivacaine and Bupivacaine Group: obtained 50 mg bupivacaine Results: The amount of morphine given postoperative was significantly decreased in meperidine group and tramadol group than bupivacaine group (P≤0.001). The time of first dosage of morphine given postoperatively had been earlier in bupivacaine group contrasted to tramadol group than meperidine group (P<0.05). Heart rate, systolic blood pressure, diastolic blood pressure at the studied times, sedation score and side effects had been insignificantly varied between the studied groups. Visual analogous scale (VAS) at rest and cough was significantly lower in meperidine group than tramadol group at 3, 6, 9, 12, 15 and 18 hours (P<0.05). VAS at rest and cough was significantly lower in meperidine group than bupivacaine group at 3, 6, 9, 12, 15, 18 hours (P≤0.001). Conclusions: The impact of the addition of intraincisional Meperidine or tramadol to bupivacaine caused adequate and prolonged analgesia. Meperidine when added to intraincisional bupivacaine provides significant analgesia better than intraincisional bupivacaine alone as lasting for a relatively long time.